2008
DOI: 10.1002/hbm.20433
|View full text |Cite
|
Sign up to set email alerts
|

Are numbers special? Comparing the generation of verbal materials from ordered categories (months) to numbers and other categories (animals) in an fMRI study

Abstract: Months, days of the week, and numbers differ from other verbal concepts because they are ordered in a sequence, whereas no order is imposed on members of other categories, such as animals or tools. Recent studies suggest that numbers activate a representation of their quantity within the intraparietal sulcus (IPS) automatically, that is, in tasks that do not require the processing of quantity. It is unclear, however, whether ordered verbal materials in general and not only numbers activate the IPS in such task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 80 publications
2
37
1
Order By: Relevance
“…It is worth noting that Eger et al (2003) found stronger activation of hIPS for number processing than for letter processing but their simple identification task did not involve processing the ordinal dimension of letters. Further support to the hypothesis that hIPS is involved in the representation and processing of non-numerical ordered sequences (Fias et al, 2007) is provided by the study of Ischebeck et al (2008), who found no significant difference in IPS between ordered generation of months and numbers, compared to the generation of non-ordered names of animals.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is worth noting that Eger et al (2003) found stronger activation of hIPS for number processing than for letter processing but their simple identification task did not involve processing the ordinal dimension of letters. Further support to the hypothesis that hIPS is involved in the representation and processing of non-numerical ordered sequences (Fias et al, 2007) is provided by the study of Ischebeck et al (2008), who found no significant difference in IPS between ordered generation of months and numbers, compared to the generation of non-ordered names of animals.…”
Section: Introductionmentioning
confidence: 92%
“…However, there is a third possible interpretation. The results of Fias et al (2007) and Ischebeck et al (2008), though suggestive, do not necessarily imply that the same neuronal populations within hIPS are involved in processing both numerical and non-numerical ordered sequences (see Jacob and Nieder, 2008, for a similar argument). The results might be an artefact due to the limited spatial resolution of fMRI and/or the limitations imposed by the conventional univariate fMRI data analysis (general linear model).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It should be noted that the specificity of hIPS for numerical processing has been criticized by some authors, who found similar patterns of activation while processing numerical and nonnumerical ordered sequences (Fias et al, 2007;Ischebeck et al, 2008), as if hIPS activation in tasks that involve the processing of numerical magnitude would be induced by the ordinal (rather than cardinal) dimension. This raises again the question of whether ordinality might be the common feature subtending the similarity between number and time and whether time is processed in the same network devoted to numbers.…”
Section: Ordermentioning
confidence: 99%
“…Digits are both visually and conceptually different from verbal materials. Brain-imaging studies have shown that processing numbers and other ordered categories (e.g., months) engages a different part of the brain than processing conceptual categories (e.g., animals; see Ischebeck et al, 2008). Young children failed to show a midlist isolation effect with digits isolated in a series of pictures (Howe, Courage, Vernescu, & Hunt, 2000).…”
mentioning
confidence: 99%